The role of hematological parameters in predicting tumor grade and stage in renal cell carcinoma patients undergoing nephrectomy - Anitha Prakasam, Karthi; Mattanchery, Dineshan Kunimmal (International Surgery Journal, 2026)
Background: The aim of this study is to evaluate the role of hematological parameters in predicting Fuhrman grade and tumor stage in renal cell carcinoma patients undergoing nephrectomy. Methods: All patients newly admitted in the Department of Genitourinary Surgery in Kozhikode Medical College with a diagnosis of renal cell carcinoma from 01 August 2020 to 31 July 2021 were included after taking informed consent and considering the inclusion and exclusion criteria. Results: Hematological parameters such as red blood cell distribution width (RDW), haemoglobin to platelet ratio (HPR), procalcitonin (PCT) and platelet to lymphocyte ratio (PLR) when correlated with the grade of cases, RDW and PLR were seen increased in high grade tumours. RDW and PLR showed statistically significant correlation with a p value of <0.001 for RDW and 0.02 for PLR. An RDW above 14.2 and PLR more than 140.69 is likely to be predictive of high Fuhrman grade. ROC curve was plotted and the mean RDW, PLR, PCT cut-off values of the patients for FG and T stage were 12.8%, 130.7, 0.24% and 13.8%, 166.01, 0.19% respectively. RDW, PLR, PCT, HPR were analyzed for any correlation for predicting whether the tumor be limited to kidney or extending outside kidney. Only RDW showed a statistically significant result with p value 0.02 and it suggests that RDW above 14.52 is suggestive of a tumor limited to kidney. Conclusions: We conclude that when hematological parameters such as RDW and PLR were correlated with grade of the tumor and RDW with the stage of the tumor. HPR and PCT didn’t show significant relation with grade of tumor.